2020
DOI: 10.1101/2020.11.19.389486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dorsal Periaqueductal gray ensembles represent approach and avoidance states

Abstract: Animals must balance needs to approach threats for risk-assessment and to avoid danger. The dorsal periaqueductal gray (dPAG) controls defensive behaviors, but it is unknown how it represents states associated with threat approach and avoidance. We identified a dPAG threat-avoidance ensemble in mice that showed higher activity far from threats such as the open arms of the elevated plus maze and a live predator. These cells were also more active during threat-avoidance behaviors such as escape and freezing, eve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…One possibility is that distinct neuronal ensembles are activated by the opposite types of social stimuli, one of which is associated with approach behavior while the other triggers avoidance. It should be noted that such an arrangement was recently demonstrated in the PAG (Reis et al, 2021), one of the main targets of the AHN (Hahn and Swanson, 2015;Semenenko and Lumb, 1999). Alternatively, the same neurons may be activated by both stimuli, but in a different manner.…”
Section: Discussionmentioning
confidence: 86%
“…One possibility is that distinct neuronal ensembles are activated by the opposite types of social stimuli, one of which is associated with approach behavior while the other triggers avoidance. It should be noted that such an arrangement was recently demonstrated in the PAG (Reis et al, 2021), one of the main targets of the AHN (Hahn and Swanson, 2015;Semenenko and Lumb, 1999). Alternatively, the same neurons may be activated by both stimuli, but in a different manner.…”
Section: Discussionmentioning
confidence: 86%
“…Z. Yang et al, 2020), we observed elevated calcium responses of LPB CCK neurons by heat stimuli (43 ° C) (Supplementary Figure 4A-D) . We then tested the response of these neurons in a predator-exposure assay, in which an awake but restrained rat was placed at one end of a rectangular arena (Reis et al, 2021; Weisheng Wang et al, 2021), and a mouse was placed at the other end, away from the rat. After perceiving the presence of the rat, mice usually exhibit risk assessment behaviors by curiously approaching and investigating the rat (Olivier, Mos, & Slangen, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence in support of a rate-coding mechanism of the PAG in the assessment of risk was shown through optogenetic activation of dlPAG CaMKIIα neurons, which evoke freezing at lower frequencies and flight at higher frequencies (Deng et al, 2016). However, population coding mechanisms may also play a part, since endoscopic calcium imaging of dlPAG neurons showed distinct neural populations that are responsive to either higher or lower threatening situations (Reis et al, 2021).…”
Section: Threat Assessment and Decision In The Pagmentioning
confidence: 99%